Preparing the Future Nutrition Professional: A Summer Internship Case Study Examining Food Systems. (14th June 2022) - Perteet-Jackson, Alissa; Jansma, Melissa; Marquart, Len; Wibbens, Katie
Abstract: Objectives: Evaluate the effectiveness of a virtual food systems internship to enhance nutrition undergraduate professional skill development and project management skills management skills. Methods: A total of five students participated in a 14-week internship via Zoom with sessions led by academic and industry professionals. Presenters provided an overview of the food system relative to their roles and function within the production of food and processing of ingredients. The virtual format allowed the students to network with experts from across the United States and to learn how to learn together. Students engaged in independent project-work and research culminating in student-led seminars to address barriers and opportunities in the food system. Students evaluated presentation styles to support development of their skills through exposure to agriculture, business, consumer, and regulatory topics. Each week students participated in facilitated dialogue to critique the presenters and communicate research findings and project progress. In addition, students reflected on how the materials and presentation impacted development of their transferable skills in the areas of communication, project management/leadership, interpersonal and intrapersonal skills, and self-management. Results: Students were introduced to the pre-farm to consumer food system broadening their understanding of the role of nutrition in food production. Based on a thematic analysis of student reflections, the themes identified include skill development in confidence, communication, working towards collective goals, and appreciation for the flexibility of the virtual format. Conclusions: Despite the impact of COVID-19 on education and training, we found that a successful internship can be conducted virtually such that students gained confidence in their ability to communicate concepts related to industry projects and production. Future work should continue to bridge the university-industry training gap. Funding Sources: None.